Rice False Smut Disease at Different Flowering Times (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this article have changed from 28-34 to 28-35.Rice false smut (RFSm) has lately been recognized as an emerging disease worldwide. Its alarming prevalence in Bangladesh in the transplant Aman rice in the last three years has been widely reported. However, there is no effective control measure against the disease in this country. We hypothesized that manipulation of flowering time in aman rice may avoid RFSm incidence. A two-year study (2014 and 2015) during T. Aman season using the widely regarded RFSm-prone variety, BRRI dhan49, across a range of flowering regime from mid-July to mid-January, demonstrated lower disease incidence in earlier (till mid-October) and later (after mid-November) part. The highest incidence of the disease was recorded when the crop flowered on 9 and 5 November in 2014 and 2015, respectively. The disease was recorded on ratoons. The peak of the infection recorded on ratoons when flowered on 7 November. To the best of our knowledge, worldwide, this is the first record of the disease on ratoons. Rainfall did not influence the disease. The relationship between the disease incidence and relative humidity and sunshine hours were significant. Avoiding flowering time during mid-October to mid-November through planting time adjustment appeared as an effective practice to escape rice false smut disease incidence in Aman season.Bangladesh Rice j. 2015, 19(2): 28-35